Excesso de peso em pilotos da aviação regular associado às características do trabalho e de saúde. - Palmeira, Magna Lúcia de Souza (2016)
Introduction: In addition to the already known causes which lead to excess weight, such as changes in lifestyle and in the food intake pattern, the decrease in sleeping time has been discussed in recent times, as well as the inversion of the sleep-wake cycle. In the occupational category of airline pilots, irregular working schedules, as well as time zone changes are common. This type of organization of working time into irregular shifts may damage the pilot¿s health, both in the physical aspect, as well as in the psychological, emotional and social ones. Among these damages, the aspects related to weight gain stand out. Commonly airline pilots invert the sleep-wake cycle and reduce the total sleeping time due to the irregular working shifts. Airplane pilots are submitted to irregular working shifts, altering the sleep-wake cycle, which may influence the appetite and the sense of satiety, thus favoring weight gain. Objective: The main objective of this study was to analyze the working conditions and the health of Brazilian regular aviation pilots. Methods: This is a cross-sectional observational study, carried out with 1.198 Brazilian regular aviation pilots. The data collection was performed by means of an online questionnaire, with socio-demographic, work, health, lifestyle and sleeping data. For the analysis of the factors associated to excess weight (overweight and obesity) Poisson regression analysis with robust variance was carried out. In all the tests P-values of less than 0.05 were considered statistically significant. The data was analyzed using the STATA 12.0 program. Results: All the pilots were male, with an average age of 39.2 years (SD = 9.8 years). In relation to body mass index (BMI) 53.7% of the pilots were considered as being overweight and 14.6% as being obese. Higher chances of being overweight were verified in people who worked night shifts between six to ten years and who had difficulty relaxing after work, being the perception of morningness a protection factor. Working night shifts between six to ten years, difficulty to relax after work, to sleep less than six hours on the time off work, to have other diagnosed diseases and to practice less than 150 minutes/week of physical activity were considered as being risk factors for obesity. Conclusion: These results point to a high prevalence of overweight and obesity in this occupational category, characterized as being a public health problem, signaling to the need for interventions for the body weight control.